Teachers’ Strategies in Integrating Digital Learning Me-dia to Achieve Basic Competencies in Islamic Education in Elementary Schools - S Sopandi; Usep Suherman (Journal of Science and Education (JSE), 2025)
This study aims to explore teachers’ strategies in integrating digital learning media to support the achievement of basic competencies in Islamic Education (PAI) at elementary schools. The research focuses on teachers’ practices at SDN Cipeundeuy, Bandung Regency, in responding to digital learning challenges amid infrastructure limitations and limited access to technology. A qualitative descriptive approach with a case study design was employed. Data collection was conducted through classroom observation, semi-structured interviews, and documentation of teaching materials. Data analysis was performed using the interactive model of Miles and Huberman, encompassing data reduction, data presentation, and conclusion drawing. The results of the study indicate that IRE teachers actively utilize digital media such as educational videos, quiz applications (Kahoot, Quizizz), and WhatsApp as a medium for distributing learning materials. The use of these media had a positive impact on student engagement and understanding of the material, as indicated by an increase in the average score from 70 to 85. Adaptive strategies were also implemented in the form of hybrid learning and digital-based projects such as infographics on Islamic values. Despite facing challenges related to limited devices and technical competencies, teachers demonstrated increased professionalism through self-directed training and collaboration in Teacher Working Groups (KKG). This study concludes that the integration of digital media can be an effective pedagogical approach in PAI learning, with the proviso that there is ongoing support for infrastructure strengthening and teacher capacity building. This study makes an important contribution to the development of contextual, participatory, and relevant digital-based religious education that meets the needs of the 21st century